2011
DOI: 10.1038/modpathol.2010.231
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblastic vasculogenic mimicry in gestational choriocarcinoma

Abstract: Angiogenesis is a characteristic feature of solid tumors, which depend on the newly formed vasculature to prevent hypoxia and to sustain uncontrolled tumor cell proliferation. In this study, we investigated the blood supply system in 10 gestational choriocarcinomas on the basis of histopathological and immunohistochemical features. In all examined cases, morphological analysis demonstrated that blood channels within the center of choriocarcinomas were surrounded by neoplastic trophoblastic cells rather than by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“…Previous studies reported the development of animal models of CC, mainly through subcutaneous injection of JEG3 cells (47). JEG3 dissemination and colonization of blood vessels were compared with non-trophoblastic tumor cells (48,49). Nevertheless, these studies were performed in non-gravid mice and cells were not injected orthotopically within the primary site of CC development, for example, the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the development of animal models of CC, mainly through subcutaneous injection of JEG3 cells (47). JEG3 dissemination and colonization of blood vessels were compared with non-trophoblastic tumor cells (48,49). Nevertheless, these studies were performed in non-gravid mice and cells were not injected orthotopically within the primary site of CC development, for example, the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…Shih showed that pseudovascular choriocarcinoma networks are established by CD31‐negative syncytiotrophoblasts, not endothelial cells . In addition, he suggested that this phenomenon may cause massive hemorrhage and necrosis, which are frequently observed in choriocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Shih showed that pseudovascular choriocarcinoma networks are established by CD31-negative syncytiotrophoblasts, not endothelial cells. 13 In addition, he suggested that this phenomenon may cause massive hemorrhage and necrosis, which are frequently observed in choriocarcinoma. However, syncytiotrophoblast-and cytotrophoblast-like cells were both focally positive for the endothelial cell marker CD31 in the present case and one previous case.…”
Section: Discussionmentioning
confidence: 99%
“…In an ongoing study, we are assessing a panel of known circulating angiogenesis factors and correlating these with the UAPI to establish drivers of angiogenesis, and with MTX-R as alternatives to UAPI. Interestingly, in a recent study Shih Ie (2011) has shown that choriocarcinomas despite their apparent vascularity, lack endothelial-lined intra-tumoural blood vessels, and instead exhibit vascular mimicry. Consequently, it is plausable that the biological drivers of this may be distinct from classical angiogenic factors (Shih Ie, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a recent study Shih Ie (2011) has shown that choriocarcinomas despite their apparent vascularity, lack endothelial-lined intra-tumoural blood vessels, and instead exhibit vascular mimicry. Consequently, it is plausable that the biological drivers of this may be distinct from classical angiogenic factors (Shih Ie, 2011). In the current study, only three patients had choriocarcinomas.…”
Section: Discussionmentioning
confidence: 99%